Analysis of amphetamine and methamphetamine contents in seized tablets from Jazan, Saudi Arabia by liquid chromatography-mass spectroscopy (LC-MS/MS) and chemometric techniques - Hassan A. Alhazmi; Waquar Ahsan; Mohammed Al Bratty; Sadique A. Javed; Karam A. El-Sharkawy; Asaad Khalid; Hussain M. Alsalem; Ahmed M. Hakami; Mohammad A. Attafi; Magbool E. Oraiby (Elsevier, 2020)
A number of illegal amphetamine tablets were seized from three different cities of Jazan province of southern Saudi Arabia and were analyzed for amphetamine and methamphetamine contents using LC-MS/MS technique. Analyses were performed using a previously reported method taking 0.1 M ammonium formate buffer (85%) and 15% acetonitrile with 0.1% formic acid as mobile phase with a total runtime of 12 min. This method was successfully applied for the routine analysis of amphetamine and methamphetamine in the seized tablets using amphetamine-D5 and methamphetamine-D5 as internal standards. Hierarchical cluster analysis was performed to establish the similarity between samples. The retention times (RT) for internal standard, amphetamine and methamphetamine were observed to be within 6.0-7.1 min. Ten tablet samples from each city were subjected to analysis and the amount of amphetamine in all the samples were found to be in the range of 9.07-14.77 mg, whereas, the amount of methamphetamine ranged from 0.12 to 0.24 mg in each tablet. Hierarchical cluster analysis showed presence of five clusters of samples indicating different characteristics and possible sources of amphetamine tablets. The largest cluster consisted of 15 samples which are expected to be of the same origin. Both amphetamine and methamphetamine are considered to be illegal products and their illegal trade and use is banned in many countries including Saudi Arabia. Therefore, there is an urgent need of strict regulations worldwide to check the illicit trafficking of these psychoactive substances and should be considered on priority.